2008
DOI: 10.4049/jimmunol.180.4.2233
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Transient Receptor Potential 5 Channel in Conjunction with Orai1 and STIM1 Allows Sr2+ Entry, Optimal Influx of Ca2+, and Degranulation in a Rat Mast Cell Line

Abstract: Degranulation of mast cells in response to Ag or the calcium mobilizing agent, thapsigargin, is dependent on emptying of intracellular stores of Ca2+ and the ensuing influx of external Ca2+, also referred to as store-operated calcium entry. However, it is unlikely that the calcium release-activated calcium channel is the sole mechanism for the entry of Ca2+ because Sr2+ and other divalent cations also permeate and support degranulation in stimulated mast cells. In this study we show that influx of Ca2+ and Sr2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 67 publications
5
74
0
Order By: Relevance
“…One possible mechanism is through Fyn-dependent phosphorylation of plasma membrane calcium channels. Some transient receptor potential channel (TRPC) family members are substrates for Src family kinase, like Fyn (Hisatsune et al, 2004;Vazquez et al, 2004) and the recent finding (Ma et al, 2008) in the mast cell line (RBL-2H3) showing that TRPC channels can contribute to mast cell calcium influx makes this a plausible scenario. Another possible mechanism could be through the generation of sphingosine-1-phosphate (S1P) by sphingosine kinase 2 (SphK2).…”
Section: A the Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible mechanism is through Fyn-dependent phosphorylation of plasma membrane calcium channels. Some transient receptor potential channel (TRPC) family members are substrates for Src family kinase, like Fyn (Hisatsune et al, 2004;Vazquez et al, 2004) and the recent finding (Ma et al, 2008) in the mast cell line (RBL-2H3) showing that TRPC channels can contribute to mast cell calcium influx makes this a plausible scenario. Another possible mechanism could be through the generation of sphingosine-1-phosphate (S1P) by sphingosine kinase 2 (SphK2).…”
Section: A the Kinasesmentioning
confidence: 99%
“…2). Recently, the use of silencing RNAi strategy and ectopic expression experiments has revealed that TRPC5 and STIM-1 cooperate to elicit both Ca 2+ and Sr 2+ influx in the mast cell line (RBL-2H3) (Ma et al, 2008), and this contributes to the enhanced calcium response needed for degranulation. This cooperation was easily distinguished from selective Ca 2+ entry induced by co-expression of STIM-1 and CRACM1/ Orai1.…”
Section: B the Calcium Apparatusmentioning
confidence: 99%
“…We must also acknowledge that we cannot exclude a role for other channel partners in the CCE complexes. It is quite feasible that a background of, for instance, certain TRPC molecules might participate in the assembly of the CCE apparatus (Yuan et al, 2007;Ma et al, 2008) the regulatory consequences of which we are studying. However, whatever the background, it is clear that in the present experimental situation, the increment in CCE regulation of AC8 is due only to the expression of STIM1 and Orai1.…”
Section: Camentioning
confidence: 99%
“…Alternatively, the negative regulatory effect could result from modulation of a channel other than Orai1. For example, Ma and co-workers recently described evidence that the Ca 2+ channel protein TRPC5 contributes to SOCE in RBL cells (Ma et al, 2008). The Ca 2+ -activated cation channel, TRPM4, negatively regulates SOCE in BMMCs (Vennekens et al, 2007) and is positively regulated by PtdIns(4,5)P 2 (Nilius et al, 2006).…”
Section: Mechanisms Of Regulation Of Camentioning
confidence: 99%